Negotiating language choice in multilingual lab meetings: voices from domestic and international students in Taiwan. Issue 1 (2nd January 2022) - Lin, Shumin
ABSTRACT: This article examines language practice in international higher education (HE) in non-Anglophone countries, with a focus on language choice and negotiation in engineering and science lab meetings among culturally and linguistically diverse students and professors. Analyses of 53 in-depth interviews with students and professors in a research university in Taiwan show that the professors addressed the linguistic diversity among domestic and international students by imposing an English policy or having an open policy for the lab meetings. Whatever the policy is, the language choice was subject to constant negotiations among all lab members, leading to dynamic flows and configurations of translanguaging. The language choice and negotiation is embedded in the local-global tensions in that local students' language preference is the local language Chinese, while international students' language preference is the global lingua franca English. The study suggests that multilingual multimodal academic communication in international HE is natural but not all language choices are equally inclusive and conducive to learning for all members. This study has provided a comprehensive picture and nuanced analyses of language choice in multilingual lab meetings. Future research with discourse data would enrich the present findings to further explicate optimal translanguaging practices in international HE.